Chorionic villus sampling for early prenatal diagnosis: Experience at a mainland Chinese hospital. (November 2014) - Han, J.; Pan, M.; Zhen, L.; Yang, X.; Ou, Y-M.; Liao, C.; Li, D-Z.
Abstract The aim of this study was to describe the experience of transabdominal chorionic villus sampling (CVS) at a mainland Chinese hospital. During a 7-year period, 1, 172 pregnant women chose to have CVS for prenatal diagnosis. Details and outcome of all of these cases were reviewed. The median maternal age was 29 years (range 19–45). The median gestational age was 12 weeks (range 10–14). Fetal karyotyping and thalassaemia couples were the main indications (97.2%). Overall, 112 (9.7%) chromosomal abnormalities were identified. There were 91 (7.8%) major chromosomal abnormalities, including autosomal trisomy in 70 patients, sex chromosomal abnormalities in 17, triploidy in two and unbalanced chromosomal rearrangement abnormality in two. Additionally, 137 fetuses with severe thalassaemia syndrome were found, including 86 homozygous β-thalassaemia, and 51 homozygous α-thalassaemia or non-deletional haemoglobin H disease. The procedure failed to obtain an adequate sample in four (0.3%) patients. There were 229 pregnancies terminated for medical indications after CVS. There were three (0.3%) potentially procedure-related fetal losses. CVS is a safe and reliable prenatal diagnostic technique. It should be one of the options available to pregnant women who require prenatal diagnosis.